Synergistic effects of polyvinylpyrrolidone and graphene oxide in thin film nanocomposite membranes for oily wastewater treatment via forward osmosis process - Hafsa Bano; Norwahyu Jusoh; Nadia Hartini Suhaimi (Scientific Reports)
Abstract Wastewater from the oil and gas industry is notoriously challenging to treat due to its complex composition. In this work, polyvinylpyrrolidone (PVP) was used to modify graphene oxide (GO) nanoparticles for the synthesis of PSf based thin-film nanocomposite (TFN) membranes through the interfacial polymerization (IP) technique, aimed at oil removal from wastewater. The composite membrane, incorporated with GO, at different PVP loadings (0.025 wt%, 0.030 wt%, and 0.035 wt%) were fabricated and characterized using FESEM, AFM, ATR-FTIR, UV–Vis spectra, tensile strength and contact angle goniometer. It is found that with the presence of PVP-GO inside the TFN membranes, it exhibited higher surface hydrophilicity due to an increment in hydroxyl and carboxyl groups in the polyamide (PA) layer, which improves the attraction between water molecules and membrane surface. TFN membrane assimilated with 0.035 wt% PVP-GO achieved 48.871 L/m2.h and flux recovery ratio of 88% of water flux with decreased contact angle up to 46° and thin film thickness of 137 nm as compared to the TFN membranes without the addition of PVP with 34.118 L/m2.h of water flux. Overall, the PVP-modified GO nanocomposite membranes in this work demonstrated promising performance for oil-in-water emulsion separation, which makes them an attractive candidate for industrial water separation especially for produced water treatment.